Strategi Manajemen Risiko Kredit Dalam Pembiayaan Umkm Dari Bank Syariah : Studi Kasus Bank Syariah Indonesia Kc Surabaya Jemur Handayani - Nur Diana; Syarif Thayib (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the credit risk management strategies implemented by Bank Syariah Indonesia (BSI) in financing Micro, Small, and Medium Enterprises (MSMEs). Credit risk remains one of the primary challenges in Islamic banking, as the profit-sharing system tends to increase the likelihood of non-performing financing (NPF). Using a qualitative approach with a case study design, data were collected through in-depth interviews with risk managers, credit analysts, and MSME actors, as well as through documentation of BSI’s risk management policies and annual reports. Thematic analysis was employed to identify patterns within the applied risk-mitigation strategies. The findings reveal that BSI adopts various approaches to reduce credit risk, including sharia-based business feasibility assessments, collaboration with microfinance institutions such as Baitul Maal wa Tamwil (BMT), and the optimization of monitoring and collection systems. The effectiveness of these strategies is influenced by internal factors—such as the quality of credit risk analysis—and external factors, including global economic conditions and regulatory changes. Overall, a comprehensive understanding of credit risk dynamics in MSME financing enables BSI to develop more effective mitigation policies. This study provides valuable insights for stakeholders in the Islamic banking sector in improving access to MSME financing, strengthening bank profitability, and maintaining the stability of Indonesia’s Islamic financial system.